Pengaruh Pengembangan Karir, Motivasi Kerja, dan Disiplin Kerja Terhadap Kinerja Karyawan di PHD Pizza Hut Delivery Palembang - Aditya, Reza; Suhada, Suhada; Novalia, Nurkardina (Peneliti.net, 2024)
This study aims to determine the effect of Career Development, Work Motivation, and Work Discipline on Employee Performance at PHD Pizza Hut Delivery Palembang. Population is a generalization domain which consists of objects/subjects with certain characteristics and characteristics determined by the researcher to be studied and conclusions drawn from there. In this study, the entire population consisted of PHD Palembang staff, totaling 35 people. Partial hypothesis test results (t) coefficient value sig. for the variable Career Development (X1) of 0.009 <0.10, meaning that Career Development has a direct positive and significant effect on Employee Performance. While the value of the coefficient sig. for the variable Work Motivation (X2) of 0.004. -So, the significance value is 0.004 <0.10, meaning that work motivation directly affects employee performance. And for the variable Work Discipline (X3) sig. 0.005, when compared with the P-value then 0.000 <0.10. Therefore the results of the hypothesis are that H¬0 is rejected and H1 is accepted, meaning that there is a positive and significant direct effect of Work Discipline on Employee Performance.